Undergraduate Gender Diversity and the Direction of Scientific Research - Francesca Truffa; Ashley Wong (CESifo GmbH, 2024)
Can diversity lead to greater research focus on populations underrepresented in science? Between 1960 and 1990, 76 all-male US universities transitioned to coeducation. Using a generalized difference-in-differences design, we find that coeducation led to a 44% increase in gender-related research publications. This increase is driven by research focused on female subjects and gender differences. While coeducation led to a compositional shift with more women and researchers interested in gender topics, much of the increase comes from male incumbent researchers shifting their research focus toward gender-related topics. The results support interaction with more diverse students and peers as key underlying mechanisms.
Keywords: J16; O31; O34; 330; gender diversity; direction of innovation; scientific research